You think you are big fish in a small pond? Perceived overqualification, goal orientations, and proactivity at work. (23rd May 2015) - Zhang, Melody Jun; Law, Kenneth S.; Lin, Bilian
Summary: Overqualification denotes situations in which job incumbents have higher qualifications than those required for the job. Drawing on the self‐regulatory perspective, we proposed that employees' perception of overqualification positively affects their proactive behavior through the mechanism of role‐breadth self‐efficacy and that this indirect effect is moderated by employees' goal orientations. We tested our hypotheses through two studies. In Study 1, we found that perceived overqualification had a positive indirect effect on employees' proactive behavior through role‐breadth self‐efficacy using a sample of 323 salespeople with a cross‐lagged panel design. In Study 2, the multi‐wave and multi‐source data from 302 teachers confirmed the indirect effect and indicated that performance goal orientation and learning goal orientation moderated the indirect relationship. Copyright © 2015 John Wiley & Sons, Ltd.